A comprehensive review of immunosuppressive drugs in pediatric dermatoses: Part I - Corticosteroids, azathioprine, and cyclosporine-A - Shiti Bose; Bhushan Madke (Wolters Kluwer Medknow Publications, 2022)
Pediatric dermatoses constitute an array of varied diseases, a few of which may require long-term treatment with immunosuppressants in the form of corticosteroids (CS) and steroid-sparing agents such as azathioprine, cyclosporine, and methotrexate. There are numerous articles mentioning long-term adverse effects of these immunosuppressants in adults, but just a few mentioning the same in the pediatric age group. This concise review focuses on the immunosuppressants commonly used for dermatoses in children and gives a comprehensive list of the various indications for use in each and associated adverse effect on long-term use. A comprehensive search was done using PubMed, Google, EMBASE, Cochrane, and MEDLINE on studies published till date on immunosuppressant use in pediatric dermatoses with special emphasis on the safety and adverse effects on long-term therapy. Only English language articles were considered. Thirty-eight articles were found, of which only 28 were selected after removing duplication and articles having no relevant information. Clinical as well as randomized double-blinded or single-blinded controlled trials, open-label studies, retrospective studies, case series, reviews, and case reports on the use of immunosuppressants in pediatric age group, including their long-term adverse effects were screened and a documented evidence was prepared, analyzed and presented in a narrative fashion to highlight the important pediatric indications for the use of the respective immunosuppressant, with special emphasis on the adverse effects on prolonged usage. The review has been divided into two parts for the reader's benefit. Part I consists of CS, azathioprine, and cyclosporine, whereas, Part II consists of methotrexate and mycophenolate mofetil.